Construction of TVET Students' Career Profile Pathways - Rasul, Mohamad Sattar; Mohd Nor, Ahmad Rosli; Amat, Salleh (Journal of Technical Education and Training, 2021)
A lucrative career and meet the personality of the individual is the dream of every human being. Yet, the diversity of human personalities causes each individual to need a different career path to obtain a career that is in line with their personalities. This study was conducted to develop different career development pathways according to the profile of each individual. This qualitative study used Multiple Case Study with Delphi technique Interview Method as the data collection method. There were 15 informants who were graduated from TVETs background and have been successful in their careers. The results of the analysis using Thematic Analysis and Fuzzy Delphi have produced Seven (7) different career paths according to profile namely Opportunist Path, Aggressive Path, Systematic Path, Cognitive Path, Conventional Path, Roe Path and Roe-Supportive Path. All these Career Routes are then agreed by experts using Focused Group Discussion techniques consisting of lecturers and alumni of TVETs. These different paths can give a new dimension to students to make their own career planning based on their personalities.